A splicing mutation in VPS4B causes dentin dysplasia I. Issue 9 (31st May 2016) - Yang, Qi; Chen, Dong; Xiong, Fu; Chen, Danna; Liu, Cuixian; Liu, Yanhui; Yu, Qiuxia; Xiong, Jun; Liu, Jinzhong; Li, Kunyang; Zhao, Lingfeng; Ye, Yuhua; et al.
Abstract : Background: Dentin dysplasia I (DDI) is a genetically heterogeneous autosomal-dominant disorder characterised by rootless teeth with abnormal pulpal morphology, the aetiology of which presents as genetically heterogeneous. Methods and results: Using a cohort of a large Chinese family with 10 patients with DDI, we mapped to a 9.63 Mb candidate region for DDI on chromosome 18q21.2–q21.33. We then identified a mutation IVS7+46C>G which resulted in a novel donor splice site in intron 7 of the VPS4B gene with co-segregation of all 10 affected individuals in this family. The aberrant transcripts encompassing a new insert of 45 bp in size were detected in gingival cells from affected individuals. Protein structure prediction showed that a 15-amino acid insertion altered the ATP-binding cassette of VPS4B. The mutation resulted in significantly reduced expression of mRNA and protein and altered subcellular localisation of VPS4B, indicating a loss of function of VPS4B. Using human gingival fibroblasts, the VPS4B gene was found to act as an upstream transducer linked to Wnt/β-catenin signalling and regulating odontogenesis. Furthermore, knockdown of vps4b in zebrafish recapitulated the reduction of tooth size and absence of teeth similar to the tooth phenotype exhibited in DDI index cases, and the zebrafish mutant phenotype could be partially rescued by wild-type human VPS4B mRNA. We also observed that vps4b depletion in the zebrafish negatively regulates the expression of some major genes involved in odontogenesis. Conclusions: This study identifies VPS4B as a disease-causing gene for DDI, which is one of the important contributors to tooth formation, through the Wnt/β-catenin signalling pathway.